2019
DOI: 10.11622/smedj.2018064
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dysplasia of the hip: why are we still operating on them? A plea for institutional newborn clinical screening

Abstract: Lack of institutionalised newborn clinical screening appears to be the root cause for the late presentation of DDH leading to open surgeries for its management. We recommend quality institutionalised newborn clinical screening to reduce the number of late presentations leading to open surgeries for DDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…5 The reasons DDH management remains non-standardized are multifactorial, for reasons such as population size and definition of incidence rates differences as illustrated by our findings, distribution of healthcare resources and infrastructure, and differing opinions on clinical exam findings suggestive of DDH. 11,20,35 One country's journey toward developing a newborn screening program highlighted several difficulties in reviewing the available literature. Singapore is one of the countries that did not have a searchable screening program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 The reasons DDH management remains non-standardized are multifactorial, for reasons such as population size and definition of incidence rates differences as illustrated by our findings, distribution of healthcare resources and infrastructure, and differing opinions on clinical exam findings suggestive of DDH. 11,20,35 One country's journey toward developing a newborn screening program highlighted several difficulties in reviewing the available literature. Singapore is one of the countries that did not have a searchable screening program.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,36 Reasons for difficulties encompassed the gap between neonatology clinical screening and orthopedic referral, concerns a typical hip at the time of neonatal screen later develops dysplasia, variations in patient population characteristics, and ongoing debates about the timing of a screening ultrasound. 10,11 The recent literature in Singapore provided an interesting look into the controversies present in a well-developed nation (ranked eighth in the global health index), which lacks a DDH screening program despite pediatric orthopedists and neonatologists' recommendations. 10,11,16,36 Our study has limitations and some study design flaws.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A local study conducted in 2015 showed that institutionalised newborn clinical screening appears to be the single most important factor for the prevention of late presentation of DDH, which leads to open surgery. (46)…”
Section: Developmental Dysplasia Of the Hipsmentioning
confidence: 99%